PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW DENGAN BERBANTUAN KARTU SOAL (QUESTION CARD) SEBAGAI UPAYA MENINGKATKAN HASIL BELAJAR SISWA (Studi Eksperimen pada Mata Pelajaran Ekonomi Kelas XI IPS SMA Negeri 1 Cikatomas Tahun Ajaran 2023/2024): (QUESTION CARD) SEBAGAI UPAYA MENINGKATKAN HASIL BELAJAR SISWA (Studi Eksperimen pada Mata Pelajaran Ekonomi Kelas XI IPS SMA Negeri 1 Cikatomas Tahun Ajaran 2023/2024) - Sopani, Aliza Nelis; Sartika, Sri Hardianti; Gumilar, Gugum (COSMOS : Jurnal Ilmu Pendidikan, Ekonomi dan Teknologi, 2025)
The problem in this study is the low learning outcomes of grade XI social studies students at SMA Negeri 1 Cikatomas and the effectiveness of the Jigsaw type Cooperative Learning Model with the help of Question Card media. The purpose of the study was to improve student learning outcomes using a quantitative approach and experimental methods consisting of planning, implementation, and evaluation stages. The research subjects included teachers and 209 grade XI students. Data collection techniques included observation, documentation, and tests, with analysis. The results showed that in the experimental class, the average pre-test score increased from 54.19 to 78.16, while in the control class it increased from 51.42 to 68.45. The Paired Sample T-test showed a 2-tailed Sig. value of 0.000 (<0.05), indicating a significant improvement in learning outcomes. The independent t-test also shows a significant difference between the experimental and control classes after treatment. Thus, the Jigsaw-type Cooperative Model with the help of Question Cards is proven to be more effective than the lecture method in improving the learning outcomes of students in grade XI IPS at SMA Negeri 1 Cikatomas Academic Year 2023/2024.